1ISG-024 Biological drugs in the treatment of immune mediated inflammatory diseases: monitoring of prescription appropriateness. (14th March 2021) - Garreffa, MR; Vitale, PP; De Franco Iannuzzi, A
Abstract : Background and importance: The introduction of biological drugs in clinical practice represents a new goal for the treatment of highly disabling inflammatory immune mediated diseases. Our region adopted the guidelines for the use of biological drugs in the rheumatology, dermatology and gastroenterology departments; specialists need to draw up the therapeutic plan to implement the prescriptive appropriateness. The Italian Drug Agency has issued a position paper recommending the prescription of biosimilars where possible. Aim and objectives: To evaluate the prescriptive trend and appropriateness of biological drugs for inflammatory immune mediated diseases in our health district also to implement the use of biosimilars. Material and methods: We analysed the therapeutic plan for biological drugs received by the territorial pharmacy of our health district (about 164 000 inhabitants). We extracted from the company database data relating to biological drugs dispensed in the period January 2018 to August 2019 and subsequently processed using an electronic worksheet, paying attention to therapeutic shifts and biosimilar drugs. Results: 556 patients underwent therapy with biological drugs, of whom 61.15% had rheumatological diseases, 29.32% had dermatological diseases and 9.53% had gastrointestinal diseases. The number of patients increased by 6.64% in the January–August 2019 period compared with 2018; similarly, the use of these medicines in terms of units in the first eight months of 2019 increased by 22.72% compared with the same period in 2018. For 11.15% of patients, there was a shift to another biological drug; in 88.71% of cases, the change was attributable to therapeutic ineffectiveness while the remaining 11.29% were passed to the relative biosimilar (Δ% 2019–2018 = +33.33%). Conclusion and relevance: Access to biologics has led to a significant improvement in patients' quality of life. Given the complexity of immune mediated inflammatory pathologies, identification of the correct therapy represents a critical issue at the first diagnosis. The use of biosimilar drugs increased during the analysis period; we therefore propose to promote the prescriptive appropriateness and to start a biosimilar drug prescription awareness programme, according to regional and national legislation, with a view to the sustainability of the health system, guaranteeing effectiveness, safety and quality for patients. At the same time, therapeutic efficacy will be evaluated in patients receiving biosimilars. References and/or acknowledgements: Conflict of interest: No conflict of interest